Long-term radiation-induced optical darkening effects in chalcogenide glasses - Kavetskyy, T.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
In this work, it is reported that the γ-irradiated (2.41 MGy accumulated dose) glasses As₂S₃ (∼2 mm thick) and Ge₁₅.₈As₂₁S₆₃.₂ (∼1 mm thick), both measured ∼10 years after γ-irradiation, exhibit radiation-induced optical darkening effect (i.e., long-wave shift of fundamental optical absorption edge). In the case of As₂S₃ glass, the observed longterm radiation-induced optical darkening effect is well comparable with that reported in literature for γ-irradiated (∼3 MGy accumulated dose) glass As₂S₃ (1.5 mm thick), measured directly after γ-irradiation. In view of practical application, this finding demonstrates the possibilities for development of innovative chalcogenide glass based long-term dosimeter systems with stable and controlled parameters. A possible general criterion for mechanisms of long-term radiation-induced structural changes in chalcogenide glasses has been also considered.